A review of the subfamily Picobiinae Johnston and Kethley, 1973 (Acariformes: Prostigmata: Syringophilidae) - Skoracki, Maciej; Sikora, Bozena; Spicer, Greg S. (Zootaxa, 2016)
The fauna of quill mites of the subfamily Picobiinae Johnston and Kethley, 1973 (Acariformes: Cheyletoidea: Syringophilidae) is comprehensively revised. All of 78 known species, which are grouped into 11 genera, are examined and diagnosed or redescribed. Data on picobiine hosts and distribution are summarized, including new host and locality records. The following new species are described: Charadriineopicobia apricaria sp. nov. ex Pluvialis apricaria (Linnaeus) (Charadriiformes: Charadriidae) from France, Neopicobia pari sp. nov. ex Periparus venustulus Swinhoe (type host) (Passeriformes: Paridae) from China, Parus major Linnaeus (Paridae) from Macedonia and Finland, and Poecile varius Temminck and Schlegel (Paridae) from Japan, Picobia magellani sp. nov. ex Scytalopus magellanicus (Gmelin) (Passeriformes: Rhinocryptidae) from Colombia, Picobia lonchura sp. nov. ex Lonchura leucogastra (Blyth) (Passeriformes: Estrildidae) from Indonesia, Picobia makoli sp. nov. ex Xiphocolaptes promeropirhynchus (Lesson) (Passeriformes: Furnariidae) from Colombia. The species Picobia polonica Skoracki, Magowski and Dabert, 2001 syn. nov. is a junior synonym of C. khulkhaskhani Kivganov and Sharafat, 1995. The following new combinations are proposed: Neopicobia ictericus (Skoracki and Glowska, 2010) comb. nov., Rafapicobia brotogeris (Fain, Bochkov and Mironov, 2000) comb. nov., and Rafapicobia ramphastos (Fain, Bochkov and Mironov, 2000) comb. nov. Keys to the all picobiine genera and species are presented, along with a check-list of picobiine species and their hosts.